Thermosensitive amphiphilic polyphosphazenes and their interaction with ionic surfactants - Ahn, Sungsook; Ahn, Sung Won; Song, Soo-Chang (ELSEVIER, 2008)
Temperature-responding physical hydrogels are promising materials as injectable drug delivery carriers which could hold useful bioactive materials inside the polymer networks for further controlled releases. Aimed at desired qualities at body temperature, those gel characteristics need to be adjusted carefully. In this point of view, surfactant is one of the useful molecules to be used by simple formulations without harmful chemical reactions. In this study, thermothickening of amphiphilic nonionic polyphosphazene solution is modified by anionic and cationic surfactants with different alkyl chains and counter-ions. Specified in the thermothickening system, a maximum viscosity (eta(max)) and a temperature at that point (T-max) are changed independently reflecting unique intermolecular interactions. At low concentration (1-9 mM) of the added surfactant, the eta(max) is maximized at 3 mM surfactant regardless of the surfactant type while the T-max is increased continuously along with the surfactant concentration. From a kinetic point of view, this 3 mM surfactant at the maximized reflects a polymer-dominating interaction and highly favorable polymer-surfactant interaction with a low selectivity in the surfactant type. However, the magnitude of the maximum viscosity (eta(max)) is dependent on the surfactant tail, which reflects the lifetime and the strength of the hydrophobic domains of the polymer network affected by the surfactants. Meanwhile, the magnitude of the T-max depended on the surfactant head group, which means the interfacial tension of the polymer solutions changed by the surfactants. At high concentration (10 and 30 mM) of the cationic surfactants added to the polymer solutions with two different viscosities, the cationic surfactants are supposed to interact either with the hydrophobic parts of the aggregated polymer with high viscosity or on the backbone of the less- or non-aggregated polymer with low viscosity. Ionic surfactants change the thermothickening of the amphiphilic nonionic polyphosphazene solution in a unique tail- or head-dependent way. Moreover, the concentration of the added surfactants and the association pattern of the pure polymer solutions are also crucial for the thermothickening phase behaviors. Temperature-responsive polyphosphazenes in this work exhibit unique and controllable interactions with ionic surfactants. (C) 2008 Published by Elsevier B.V.
Keywords: CRITICAL SOLUTION TEMPERATURE; THERMOREVERSIBLE GELATION; ELECTRICAL-CONDUCTIVITY; N-ISOPROPYLACRYLAMIDE; FLUORESCENCE PROBE; AQUEOUS MIXTURES; DODECYL-SULFATE; BLOCK-COPOLYMER; SELF-DIFFUSION; PHASE-BEHAVIOR